2022
DOI: 10.1038/s41467-022-30492-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of progenitor cell propagation during Drosophila tracheal remodeling

Abstract: Adult progenitor cells in the trachea of Drosophila larvae are activated and migrate out of niches when metamorphosis induces tracheal remodeling. Here we show that in response to metabolic deficiency in decaying tracheal branches, signaling by the insulin pathway controls the progenitor cells by regulating Yorkie (Yki)-dependent proliferation and migration. Yki, a transcription coactivator that is regulated by Hippo signaling, promotes transcriptional activation of cell cycle regulators and components of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…3j and Supplementary Fig. 4d ), which is in fitting with hormonal control of tracheal progenitors by insulin 31 . The cut -expressing subpopulation of PCs was verified by an enhancer trap Gal4 line and an antibody against Cut (Fig.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…3j and Supplementary Fig. 4d ), which is in fitting with hormonal control of tracheal progenitors by insulin 31 . The cut -expressing subpopulation of PCs was verified by an enhancer trap Gal4 line and an antibody against Cut (Fig.…”
Section: Resultssupporting
confidence: 52%
“…To assess the accuracy of clustering, we compared the identified marker genes with results from cell-type-specific transcription profiles. First, a correlation analysis of gene expression showed that the PC cluster displayed the highest similarity with the transcriptomic profile obtained from bulk RNA-seq of progenitor cells 31 (Fig. 1e ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations